Pathological and clinical investigations of an outbreak of Blackleg disease due to C. chauvoei in cattle in Punjab, Pakistan - Riaz Hussain; M Tariq Javed; Iahtasham Khan; Abu Baker Siddique; Bilal Aslam; Abdul Ghaffar; Narmeen Tariq; Abdul Qayyum; Gamal Wareth (Journal of Infection in Developing Countries)
Introduction: Clostridium chauvoei (C. chauvoei) is an anaerobic, histotoxic Gram-positive, bacterium causing fatal myonecrosis in livestock with high mortalities. The disease is common in dairy animals, but little is known about the pathophysiology of the disease in exotic (non-native) animals kept under local conditions in Pakistan.